(3OjhGf Pj GdQeI (B/s - (3GdNWjH GdJHQjRj, jMji Hf Ydj Hf eMeO,s 421-502 (3g`(B.s ((3HjQhJ (B:s (3OGQ GdcJGH GdYQHj,s, 1996)
(3jJfGhd GdcJGH JQLeI GdTGYQ hTYQg hjJVef GdOjhGf GdNGU Hg(B.s
Keywords: (3GdTYQ GdYQHjs -- (3GdYUQ GdCehj, (B661-750s